Rare mutations in the complement regulatory gene CSMD1 are associated with male and female infertility - Arthur S. Lee (Nature Portfolio, 2019)
Many molecular and physiological mechanisms in the regulation of fertility are shared between female and male mammals. Here, Lee et al. report an association of CNVs in CSMD1 with early idiopathic menopause in women and show that loss of Csmd1 leads to gonadal dysfunction in both male and female mice.